S128 Analysis of volatile biomarkers within exhaled breath for the diagnosis of pneumonia. (16th November 2010) - Boshier, P R; Mistry, V; Cushnir, J R; Curtis, S; Elkin, S; Kon, O M; Marczin, N; Hanna, G B
Abstract : Introduction: Whilst pneumonia is a common condition affecting both medical and surgical patients there is currently no definitive diagnostic test. One novel approach may be through the non-invasive analysis of volatile metabolites within exhaled breath, released either by pathogens or host cells. The objective of this study was to delineate the metabolic phenotype of the exhaled breath of patients with community acquired (CAP) and post-operative pneumonia. Methods: Breath samples were collected from patients with a confirmed diagnosis of CAP (n=26). Targeted analysis of six prominent breath metabolites was performed by selected ion flow tube-mass spectrometry. Metabolites found to be significantly different in the breath of CAP patients were subsequently investigated in patients undergoing both major abdominal and thoracoabdominal surgery (n=40). Receiver operating characteristic (ROC) analysis of putative pneumonia biomarkers was performed in an independent cohort of patients with suspected CAP (n=21). A diagnosis of pneumonia was established through fulfilment of pre-defined radiological, microbiological, haematological and clinical criteria. Results: Compared to healthy controls, CAP patients had significantly lower breath levels of hydrogen cyanide (6 vs 14ppb, p=0.001) and isoprene (72 vs 111ppb, p=0.014). Patients who developed postoperative pneumonia (n=8) had significantly lower levels of hydrogen cyanide within their breath compared to both those patients who had an uncomplicated recovery (4 vs 13ppb, p=0.008) and healthy controls. Whilst patients who underwent thoracoabdominal compared to abdominal surgery had higher breath levels of isoprene at both 96 (114 vs 176ppb, p=0.02) and 168 h (119 vs 176ppb, p=0.02) following surgery, this did not correlate with the onset of pneumonia. ROC analysis of hydrogen cyanide and isoprene are displayed in Abstract S128 Figure 1 . In both medical and surgical patients there was no significant change in the levels of other examined breath metabolites: acetone, ethanol, propanol and acetic acid. Conclusions: Results provide evidence that the levels of several prominent breath metabolites, which are potentially related to bacterial activity and lung injury, are significantly altered in patients with this disease. Breath analysis may therefore provide a novel, non-invasive and reliable strategy for the diagnosis of pneumonia.